The Effectiveness of GIST (Generating Interaction between Schemata and Text) and KWL (Know, Want to Know, Learned) Strategies on Students English Literacy towards Learning Motivation - Saepudin, Aep; Sulistyorini, Sri; Utanto, Yuli (Innovative Journal of Curriculum and Educational Technology, 2019)
Reading and writing abilities give the benefit for improving knowledge on integrated English information, where the information is needed to support in this era. It encourages the integration of learning strategies to improve the ability of English literacy. The research has purposed to (1) analyze the effectiveness of learning strategies in the ability of English literacy, (2) analyze the motivational learning influences the student towards English literacy ability, (3) analyze English literacy ability uses GIST strategy and KWL strategy towards learning motivation. The research method used a mix method (quantitative and qualitative) with concurrent embedded research design. The research population was the eight classes of SMPN 1 Lebakwangi. Analyzing the results showed that using GIST strategy was more effective on English literacy than KWL strategy; GIST strategy assisted the students in sorting and selecting vocabularies for classifying the important information so that it could conclude information to facilitate the understanding. The benefit of this research was to support as a reference in the learning of English literacy and to add the insight for improving English literacy ability to integrating GIST strategy and KWL strategy in the learning activity. Moreover, the use of learning strategies promoted students for critical thinking in processing and developing information that was appropriated to them.